Comparation of Diets Used for Larviculture of Meagre (Argyrosomus regius Asso1801) - Kesbiç, Osman Sabri; Yalgın, Ferhat; Acar, Ümit; Gültepe, Nejdet; Dorlay, Hakan Galip; Gültepe, Mehmet İrşad (Sciencedomain International, 2016)
This investigation compared the suitability of different diets for larviculture of meagre ( Argyrosomus regius ). For this purpose, wild fish were caught with longline and subsequently fed either a commercial diet or a mollusc diet. After two years, there was a significant difference between the two diets in the body weight but not the survival rate of the fish ( P<0.05). Both the weight gain and the FCR were significantly higher in fish that were fed the commercial diet compared with those fed Original Research Article
Keywords: 2. Zero hunger; 14. Life underwater